Resources and performance rates of medical organizations providing medical care in the field of dermatovenereology in the Russian Federation in 2016–2022 - Alexey A. Kubanov; Elena V. Bogdanova (Vestnik Dermatologii i Venerologii, 2023)
The paper describes changes in resources and performance of medical organizations providing medical care in the field of dermatovenereology in 20162022. The dynamics of the main rates of the service was analyzed, and the rates achieved in 2022 were compared with those before the pandemic of a new coronavirus infection. The rates of the provision of the population of the Russian Federation with dermatovenereologists, 24-hour and daytime dermatovenereological beds are presented. The analysis of the volumes of dermatovenereologic medical care dynamics provided in outpatient, inpatient and day hospital conditions was carried out. The dynamics of incidence of sexually transmitted infections is described, contribution of syphilis cases among foreign citizens to syphilis rates is presented. The changes in prevalence and incidence rates of diseases of the skin and subcutaneous tissue, as well as atopic dermatitis, psoriasis, contact dermatitis, other dermatitis, localized scleroderma, and discoid lupus erythematosus are analyzed.